2020
DOI: 10.3390/jcm9010264
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Taste Receptor 2 Subtypes in Human Testis and Sperm

Abstract: Taste receptors (TASRs) are expressed not only in the oral cavity but also throughout the body, thus suggesting that they may play different roles in organ systems beyond the tongue. Recent studies showed the expression of several TASRs in mammalian testis and sperm, indicating an involvement of these receptors in male gametogenesis and fertility. This notion is supported by an impaired reproductive phenotype of mouse carrying targeted deletion of taste receptor genes, as well as by a significant correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…TAS2R14 was indicated as the receptor that mediates the chloroquine-induced effect on [Ca 2+ ] i in human myometrial cells. Most recently, a study on semen cells and testis tissue was conducted by Governini et al [ 38 ]. Sperm was donated by 15 Caucasian males undergoing fertility examination.…”
Section: Bitter Taste Receptors In Other Systems and Diseasesmentioning
confidence: 99%
“…TAS2R14 was indicated as the receptor that mediates the chloroquine-induced effect on [Ca 2+ ] i in human myometrial cells. Most recently, a study on semen cells and testis tissue was conducted by Governini et al [ 38 ]. Sperm was donated by 15 Caucasian males undergoing fertility examination.…”
Section: Bitter Taste Receptors In Other Systems and Diseasesmentioning
confidence: 99%
“…For example, T1R3 is highly expressed in swine testicular tissues, especially in spermatogenic cells [3]. In mice, T1R3 and its related molecules, T1R1, G αgust , and taste receptor family 2 subunit 5 (T2R5), were primarily detected in developing haploid spermatids [4,5]. These molecules are localized in testicular Leydig cells, epididymal spermatozoa and semen [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, T1R3 and its related molecules, T1R1, G αgust , and taste receptor family 2 subunit 5 (T2R5), were primarily detected in developing haploid spermatids [4,5]. These molecules are localized in testicular Leydig cells, epididymal spermatozoa and semen [4][5][6]. Interestingly, many initial components of sweet/umami taste signaling cascades, such as PLCβ2, G protein γ13 subunit (Gγ13), and transient receptor potential channel M5 (TRPM5), are also expressed in testicular Leydig cells and late spermatogenic cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that OR4C13, MOR23, OR1E2, and OD1 have been localized in testes of human [ 10 ], mouse [ 11 ], dog [ 12 ], and rat [ 13 ] respectively. Similarly, TAS2R3, TAS2R124, and α-gustducin have been localized in testes of human [ 14 ], mouse [ 15 ], and pig [ 16 ]. These ORs and TRs can modulate the motility, fertility, and survivability of sperm, and are even involved in gametogenesis at mitotic and meiotic levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, TAS2R3, TAS2R124, and α-gustducin have been localized in testes of human [ 14 ], mouse [ 15 ], and pig [ 16 ]. These ORs and TRs can modulate the motility, fertility, and survivability of sperm, and are even involved in gametogenesis at mitotic and meiotic levels [ 14 ]. Egg releases chemicals to attract sperm cell and existence of chemoattractant gradient give cues about interaction of sperm-egg through chemotaxis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%